2016
DOI: 10.3390/en9070570
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Research on Large Scale Modern Vertical Axis Wind Turbines at Uppsala University

Abstract: This paper presents a review of over a decade of research on Vertical Axis Wind Turbines (VAWTs) conducted at Uppsala University. The paper presents, among others, an overview of the 200 kW VAWT located in Falkenberg, Sweden, as well as a description of the work done on the 12 kW prototype VAWT in Marsta, Sweden. Several key aspects have been tested and successfully demonstrated at our two experimental research sites. The effort of the VAWT research has been aimed at developing a robust large scale VAWT techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 58 publications
(61 reference statements)
0
27
0
Order By: Relevance
“…Researchers at Uppsala University developed a direct-drive, variable-speed, multi-pole, synchronous permanent magnet (PM) generator, which they used on several small three-bladed experimental vertical axis wind turbines (VAWTs) [48,49]. The concept was upscaled by Vertical Wind AB, a spinoff from the university's VAWT research, which started in 2002, and installed a 200-kW prototype near Falkenberg in 2010 that is still operational (see Figure 4).…”
Section: Vertical Windmentioning
confidence: 99%
“…Researchers at Uppsala University developed a direct-drive, variable-speed, multi-pole, synchronous permanent magnet (PM) generator, which they used on several small three-bladed experimental vertical axis wind turbines (VAWTs) [48,49]. The concept was upscaled by Vertical Wind AB, a spinoff from the university's VAWT research, which started in 2002, and installed a 200-kW prototype near Falkenberg in 2010 that is still operational (see Figure 4).…”
Section: Vertical Windmentioning
confidence: 99%
“…The aerogenerator design operates at a significantly lower elevation than the HAWT and still achieves reasonable aerodynamic efficiency with a power coefficient of 0.38, and with a significantly lower overturning moment and centre of gravity than the HAWT. Figure 13a [56]. Researchers at Uppsala university identified that the primary failure in VAWT is gearbox, and direct drive will curtail the downtime and maintenance cost by eliminating the gearbox.…”
Section: Aerogeneratormentioning
confidence: 99%
“…Hence, the focus is on the design of the direct drive synchronous generators suitable for H-rotors. The 36-pole generator developed, as shown in Figure 13b [56], was made of a neodymium-iron-boron permanent magnet rotor to withstand high overload capacity. The variable speed control is achieved by connecting the generator to the frequency drive.…”
Section: Aerogeneratormentioning
confidence: 99%
“…Independent of changes in wind direction, the operation is distinguished by turbine wind power installation with a vertical orientation of the turbine axis. In these wind power installation the turbine work due to the forces of resistance to the air flow [3]. However, the main problem of turbine wind power installation of both types is the unpredictability of wind, speed and strength of wind gusts, often changing in short periods of time.…”
Section: Introductionmentioning
confidence: 99%